What effect does the presence of sustainability and traceability certifications have on consumers of traditional meat products? The case of Iberian cured products in Spain. (May 2022) - Gaspar, Paula; Díaz-Caro, Carlos; del Puerto, Inés; Ortiz, Alberto; Escribano, Miguel; Tejerina, David
Abstract: The objective of this study was to determine the differences in the behaviour and perception of consumers from three regions in Spain with different levels of Iberian ham consumption (high, medium and low) on the attributes related to traceability and differentiated quality certifications. The study was carried out with a sample of 1501 consumers using an online questionnaire in which respondents were asked about their consumption habits regarding cured products and a choice experiment for Iberian ham was performed. The results showed that consumers give greater utility to the attributes of mandatory certification established for Iberian products (quality standards) and to the price, followed by nonmandatory quality certifications (organic, animal welfare, carbon footprint, and PDO). Specifically, animal welfare certification has been the most valued in all areas, especially in the areas with the lowest consumption. Highlights: The main reason for not consuming ham was its price. "I can't find it" was a major reason for non-consumption of loin and shoulder. The Quality Standard was the most important quality attribute. Regional differences in habits and attribute valuation are were slight. The most useful quality certification was for animal welfare, followed by organic.